2022
DOI: 10.1177/02697580221088340
|View full text |Cite
|
Sign up to set email alerts
|

System-based victim advocates identify resources and barriers to supporting crime victims

Abstract: Often left out of conversations around criminal justice reform are the victims of violent crimes. One group of people who have the needs of crime victims at the forefront of their work are victim advocates. The current study examines barriers and resources for victim advocates in being able to do their work of supporting crime victims. Through interviews with nine system-based victim advocates points of intervention are identified, which if improved would allow victim advocates to better be able to support vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In conjunction with the Politics of Difference, Young's Social Connection Model proposes that the same structure which creates inequalities for certain groups can simultaneously advance the opportunities and influence of other groups [81]. This highlighting of structural inequalities Multiple Statuses: (tally statuses below) [115][116][117][118][119] Poverty [120,121] Intellectual Disability [122,123] Physical Disability [124,125] Chronic Health & Chronic Mental Health [126,127] Addiction, including Neonatal Abstinence [128,129] Lifelong Caregiver [130,131] Foster Experience [132,133] Indigenous/ Aboriginal [134,135] Survivor of Abuse [136,137] Victim of Crime [138,139] Incarceration [140,141] Homelessness or Street/Shelter Experience [142,143] Race [144,145] Rural or Isolated Geography [146,147] Ageism: Children & Seniors [148] Gender [149,150] Hayvon International Journal for Equity in Health (2024) 23:106 is complemented by Young's argument for Five Faces of Oppression, which categorizes inequalities into: economic exploitation, socio-economic marginalization, powerlessness over one's work, cultural imperialism, and systematic violence [55]. In combination, Young's theories of social justice informs the synthesis of constructs number 1, 3, 5, 6, 7, 8.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
“…In conjunction with the Politics of Difference, Young's Social Connection Model proposes that the same structure which creates inequalities for certain groups can simultaneously advance the opportunities and influence of other groups [81]. This highlighting of structural inequalities Multiple Statuses: (tally statuses below) [115][116][117][118][119] Poverty [120,121] Intellectual Disability [122,123] Physical Disability [124,125] Chronic Health & Chronic Mental Health [126,127] Addiction, including Neonatal Abstinence [128,129] Lifelong Caregiver [130,131] Foster Experience [132,133] Indigenous/ Aboriginal [134,135] Survivor of Abuse [136,137] Victim of Crime [138,139] Incarceration [140,141] Homelessness or Street/Shelter Experience [142,143] Race [144,145] Rural or Isolated Geography [146,147] Ageism: Children & Seniors [148] Gender [149,150] Hayvon International Journal for Equity in Health (2024) 23:106 is complemented by Young's argument for Five Faces of Oppression, which categorizes inequalities into: economic exploitation, socio-economic marginalization, powerlessness over one's work, cultural imperialism, and systematic violence [55]. In combination, Young's theories of social justice informs the synthesis of constructs number 1, 3, 5, 6, 7, 8.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
“…Effective partnerships across disciplines have been found to play a primary role in helping crime victims (De La Rue et al, 2023). However, both community advocates (Kolb, 2012) and campus-based advocates (Brubaker & Keegan, 2019) indicate that their work is often devalued by other professionals.…”
Section: Discussionmentioning
confidence: 99%
“…How campus-based victim advocates perceive institutional response may be influenced by the strength of these relationships within their campus community. In a qualitative study of victim advocates based in the criminal justice system, stronger partnerships were identified by respondents as a key to effectively helping crime victims (De La Rue et al, 2023). However, campus-based victim advocates have indicated that their expertise is devalued, compared to attorneys and administrators, even those who may not have Title IX experience (Brubaker & Keegan, 2019).…”
Section: Factors Related To Perceptions Of Institutional Responsementioning
confidence: 99%
See 1 more Smart Citation
“…High caseloads and burnout place advocates at a significant risk for mental health challenges. Jurisdictions must provide adequate funding to increase the number of advocate positions so that these professionals can provide a higher level of care, while reducing their chance of burnout (De La Rue, Ortega, Castro Rodriguez, 2023). Therefore, increasing awareness may help to advocate for more positions, and as a result, spread the caseloads across more individuals.…”
Section: Macro Level Interventionsmentioning
confidence: 99%

We Are Humans Too

De La Rue,
Ortega,
Castro Rodriguez
2024
jsacp
Self Cite